Traits of Historical Research in Islamic Architectural Studies: Islamic Art and Architecture (650-1250) - Shahani, Mohammadhossein (Sinektika: Jurnal Arsitektur, 2025)
This paper investigates the traits of historical research in the context of Islamic architectural studies. For this purpose, it focuses on the distinguished book "Islamic Art and Architecture (650-1250)" and argues that these traits receive significant attention in the book. The paper begins by examining the book authors' statements to draw insights from their work plan. Underscoring the necessity of evidence-based reporting, it highlights chief facts related to the traits within the context of Islamic architecture. By analyzing their reporting and the facts, the paper unveils the principles devised for studying Islamic architectural history. It demonstrates that historians of Islamic art and architecture can employ various means to unearth evidence from the past. It delineates how the objectives of studying Islamic architecture can align with the interpretation of historical facts. It also discusses the criteria of periodization offered for dealing with the history of Islamic art and architecture, explaining the aspects of chronological categories in the book. Based on the principles, the paper finally presents suggestions for augmenting the traits in researching Islamic architecture.